Communist pigs : an animal history of East Germany's rise and fall - Fleischman, Thomas (Weyerhaeuser environmental book., 2020)
"Communist agriculture-from the perspective of the pig. In Communist Pigs, Thomas Fleischman traces the rise and fall of the German Democratic Republic from the perspective of one animal, Sus scrofa, or the pig. His goal is to offer a deeper understanding of the development of industrial agriculture in the twentieth century by looking at how the transformation from farm to factory occurred on the Communist side of the Iron Curtain. The pig occupied a key position in the regime's attempts to create and sustain a modern, industrial food system. (In the mid-1980s, East Germans consumed nearly 200 pounds of pork per capita each year.) The pig is an incredibly adaptive animal, and Fleischman follows pigs through three different social roles. First and foremost, the industrial pig, as the conditions of factory farming demanded a new breed that also reduced the species genetic diversity. But also the wild boar, whose overpopulation was a direct outgrowth of agricultural development rather than a conservation success story and the garden pig, reflecting the regime's shifting attitude toward private, small-scale farming. These animal histories reframe narratives about state socialism, the Cold War, and industrial agriculture. By paying attention to the factory farm, the backyard garden, and the industrial forest, we can see how East Germany's economy and environment became enmeshed within global exchanges of meat, grain, oil, and capital. Fleischman argues that agriculture under communism came to be indistinguishable from capitalist agriculture, and that pigs provide a clear case study of this convergence. It also sheds light on the reasons behind the GDR's environmental and political collapse, and acts as a warning about the high cost of cheap food in our present and future"--